Some new classes of generalized difference strongly summable n-normed sequence spaces defined by ideal convergence and Orlicz function - Kilicman, Adem; Borgohain, Stuti (Hindawi Publishing Corporation, 2014)
We study some new generalized difference strongly summable n-normed sequence spaces using ideal convergence and an Orlicz function in connection with de la Vallèe Poussin mean. We give some relations related to these sequence spaces also.